LEGAL POSITION OF MEMORANDUM OF UNDERSTANDING IN CONTRACT LAW IN INDONESIA - AMIN SLAMET (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
This paper aims to determine the basic understanding of the MoU and the legal position of the MoU in contract law in Indonesia. The research method used normative legal research, with a statutory approach. Normative research is legal research conducted by researching and reviewing library materials or secondary data. Secondary data in the form of primary legal materials, secondary legal materials, and tertiary legal materials or non-legal materials, all the collected materials are then analyzed qualitatively, in accordance with the study of the basic understanding of the MoU and the legal position of the MoU in treaty law in Indonesia in this paper. The results of the study indicate that the MoU is a legal document in which it explains the preliminary agreement between the two parties and is the basis for drafting future contracts. In general, MoU are made as the first step in making a cooperation contract or a more binding agreement between two parties. The binding force between the MoU and the agreement is the same, because the MoU is made based on the agreement of the parties who will bind themselves to the contents of the MoU, and is made by fulfilling the legal requirements of an agreement as stipulated in Article 1320 of the Civil Code. The legal basis used in the practice of making and implementing MoUs in Indonesia is based on the principle of freedom of contract in Article 1338 of the Civil Code. The MoU is an indirect statement of approval of its relationship with other agreements, both verbally and in writing. It also shows that the MoU is an engagement because based on Article 1233 of the Civil Code, each engagement is born good because of the agreement.